THE BUSINESS PERSPECTIVES STRATEGY TOWARDS THE TKI (INDONESIAN MIGRANT WORKERS) MARKET - Sihombing, Haeryip; Yaakob, Moh. Yuhazri; Safarudin, Mochamad (Journal of Indonesian Economy and Business, 2011)
The business prospects and opportunities of the migrant workersâ (TKI) market are stillÂ wide open. This is shown by the year to year remittances incremental of TKI thatcorresponds to the beneficial opportunity of the business players to optimize theirÂ exploration of this market. In reality, the current efforts and strategy in this exploration,however, are still not utilised effectively in terms of competitive advantage. Therefore theÂ initiative strategy towards product differentiation and innovation of the offered serviceÂ should be explored and optimised based on the sustainable beneficial prospects for theÂ business. As described briefly in this paper through a case of business innovation towardsÂ differentiation, the proposed strategies such as localization and two-sided markets areÂ required for business organisations to unlock their product innovation strategies towardsÂ TKI (as their customer) through the innovative solution against the poverty.Keywords: TKI, remittance, poverty, differentiated, solution